Biodiesel production from waste cooking oil using magnetic bifunctional calcium and iron oxide nanocatalysts derived from empty fruit bunch - Ibrahim, Naeemah A.; Rashid, Umer; Hazmi, Balkis; Moser, Bryan R.; Alharthi, Fahad A.; Rokhum, Samuel Lalthazuala; Ngamcharussrivichai, Chawalit (Elsevier, 2022)
Magnetic bifunctional nanocatalyst supported on activated carbon (AC), CaO-Fe2O3/AC was synthesized via wet impregnation method and was utilized for catalytic transesterification of waste cooking oil (WCO). A series of characterization techniques were performed to determine acid-base properties, magnetism, thermal stability, crystallinity, chemical composition, surface properties, and morphology of the catalyst. The BET analysis showed that the CaO-Fe2O3 catalysts had specific surface areas and pore sizes (∼5 nm) that were suitable for the transesterification reaction. The optimized catalyst, CaO(10%)-Fe2O3(10%)/AC, possessed significant acidity and basicity desorption of 18532 μmol g−1 and 2653 μmol g−1, respectively, which contributed to maximum biodiesel yield of 98.3% at the following reaction conditions: 3 wt%, catalyst loading, 18:1 methanol to oil molar ratio and at 65 °C for 3 h of reaction. Furthermore, the magnetism of CaO(10%)-Fe2O3(10%)/AC was 7.59 emu/g, which facilitated high recovery rates from the reaction mixture by magnetic decantation. Reusability experiments revealed a high catalytic stability (FAME yield > 80%) for at least six consecutive cycles. Biodiesel confirmation by Fourier transform infrared spectroscopy and 1H-nuclear magnetic resonance spectroscopy showed a strong C=O absorption band at 1774 cm--1 and a singlet methoxy proton signal at 3.7 ppm. Lastly, fuel properties analysis met the American biodiesel standard ASTM 6751 with low kinetic viscosity of 3.42 mm2s−1 and flash point of 134 °C.